Supernumerary tooth in the jaw, diagnosis, and treatment: A clinical case study (Research, Society and Development, 2024)
The research in question reports a clinical case of an impacted supernumerary tooth in the jaw, a circumstance rarely found compared to its most common occurrence, which is in the maxilla. This study aims to describe, through a clinical case, the clinical and radiographic characteristics of hyperdontia, presenting its diagnosis and surgical treatment. The initial analysis of the supernumerary tooth took place using a panoramic radiography, a cone-beam computed tomography (CBCT) was requested to analyze the exact location and plan the surgical intervention. The surgery consisted of the careful extraction of the impacted supernumerary tooth, using osteotomy and odontosection techniques to minimize the risk of damage to adjacent teeth, such as cyst formation and root resorption. The appropriate surgical strategy, using CBCT, became essential for the success of the procedure. Early investigation through radiographic examinations is primordial to avoid complications associated with the existence of supernumerary teeth. The present study emphasizes the importance of accurate diagnosis and careful monitoring.